Perceptual learning - Haslam, Carol; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1973)
Discusses about the relationships between perceptual and conceptual functioning in the learning
Converted into VHS 1/2 in.
Title from title screen
Executive producer, Michael Philps ; graphic design, Haydon Yong
Speaker : Cliff Holloway
Keywords: Perceptual learning; Perception -- physiology; Learning -- physiology